PENGARUH PEMBELAJARAN ONLINE MENGGUNAKAN VIRTUAL EKSPERIMEN TERHADAP MOTIVASI BELAJAR SISWA PELAJARAN IPA KELAS IX SMP - Inggrid Lady Febimelinda; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to describe the effect of experiments using learning media in the form of a virtual laboratory in terms of student learning motivation on static electricity material. The research was conducted at SMP Negeri 7 Tualang for the Academic Year 2021/2022. The research subjects were 30 students in class IX.1 and IX.2 using purposive sampling technique. The type of research is descriptive qualitative which identifies changes in learning motivation before and after using the virtual lab using a test instrument. The design of this research is a one shot case study. The instrument in this study used a closed questionnaire with a Likert scale. The data were analyzed with the help of SPSS version 25 to determine the normality of the questionnaire data and whether or not the sample distribution was homogeneous. The results of this study indicate that there is an effect of student motivation after learning science using a virtual lab. The use of a virtual lab affects learning motivation with a comparison of 29% before using a virtual lab and 74% after using a virtual lab from the criteria for learning motivation scores. It can be concluded in this study that students' learning motivation on static electricity material has a significant effect on students' learning motivation.Key Words : Covid-19 pandemic, online learning, Virtual Experiments, and Motivation